Happiness forever : a novel - Faith, Adelaide, 1975- (Farrar, Straus and Giroux, 2025)
"A debut novel, at once funny and tender, about a woman infatuated with her therapist. Sylvie is happy only when she's in therapy. This is because Sylvie is in love with her therapist; she thinks about her every second they're not together (roughly 167 hours and 10 minutes per week). In that room, Sylvie is able to talk about everything: the false hope promised by eighties music; what a dog's inner life is really like and how sad, she, Sylvie is, outside that room. She's aware she has an obsession, but whether it's some flavor of erotic transference or a lost person's need to connect, Sylvie isn't sure. Outside therapy Sylvie has what she considers to be a small life: a job as a veterinary nurse, companionship from her tattoo artist friend via text, and seaside walks with her brain-damaged dog, Curtains. But maybe therapy is making a difference, inviting her to imagine possibilities -- possibilities that include a new friend she meets on the beach. When the therapist starts to prepare Sylvie for the terrible fact that all treatment has to come to an end, Sylvie can't stop herself from imagining sleeping in her car parked outside the therapist's house. That won't work. She has to be brave. Be brave, Sylvie! We love you. In this wonderful, hilarious, stunning debut, Adelaide Faith captures the vulnerability, difficulty and joy of personhood, of being a person, of being alive."--